Pengaruh Financial Literacy, Financial Behavior, Financial Attitude, Dan Demografi Terhadap Perilaku Konsumtif Pada Generasi Z - Dyah Rini Prihastuty; Sri Rahayuningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of financial literacy, financial behavior, financial attitude, and demographics on consumer behavior among students at the Faculty of Economics and Business, University of 17 August 1945 Surabaya. This research used a questionnaire with a research sample of 100 students, using a purposive sampling technique. Data analysis in this research used multiple regression with the help of the SPSS program.The results of this research show that financial literacy has no significant effect on consumptive behavior, financial behavior has a significant effect on consumptive behavior, financial attitude has a significant effect on consumptive behavior, and demographics has no significant effect on consumptive behavior among students at the Faculty of Economics, University of 17 August 1945 Surabaya.